Las políticas de salud y prevención de enfermedades en los estudiantes de la Universidad Estatal de Milagro UNEMI. - Gavilánes Peralta, Víctor Harold (2015)
This study aims to determine the degree of existence of health policies at the State University of Milagro, UNEMI and how it relates to the risks of diseases in the students of the institution. The applied research is qualitative type, the method of investigation is hypothetical-deductive and as investigative techniques to survey and interview will be used. Scientific research will be carried out on a sample of 365 students from the State University of Milagro UNEMI, plus interviews applied to employees of the Student Welfare Unit, who with their contributions will lights to developing solutions to alleviate the current problems experienced University on Health, well observing pathology reports that handle general practitioners where the most common diseases among students evidenced. The relevance of the research is the need to determine how important it is to implement efficient health policies in the community of college students UNEMI, and how these might improve performance and academic performance in them to improve their health condition . The proposal is to carry out a strategy guide for the promotion of health culture aimed at the student community for a Unemi Healthy, where strategies among which psychosocial factors, type of food, snuff, drugs covering determined, environmental, consumption of alcohol. The contents of this guide have been constructed from a review of international literature and national experience in the field, interviews with key people, focus groups and work with expert groups.